Penerapan Strategi Pembelajaran Contextual Teaching And Learning Untuk Meningkatkan Komunikasi Belajar Matematika (PTK Pembelajaran Matematika Kelas VIII B SMP Muhammadiyah 10 Surakarta) - NGATINI, NGATINI, Prof. Dr. Sutama, M.Pd, Dr. Tjipto Subadi, M.Si (2013)
This study aims to describe the implementation of the communication strategy of learning mathematics teaching and learning is contextual learning in class VIII BSMP Muhammadiyah 10 Surakarta. This type of research in this study is the PTK (Penelitian Tindakan Kelas) Subjects receiving action is class VIII BSMP Muhammadiyah 10 Surakarta, amounting to 10 and 31 students are subject giver action VIIIB grademath teacher SMP Muhammadiyah 10 Surakarta. Data collection was conducted through observation, field notes, and documentation. To ensure the validity of the data, using the technique of triangulation. The data analysis technique in descriptive qualitative flow method comprising data reduction, data presentation, and conclusion. The results showed an increase in communication students in learning mathematics. It can be seen from the students who 1) ability in writing before action 25.8% and after the acthad increased by 77.4%, 2) verbal ability measures 16.1% before and after the act had increased by61.2%, 3) the ability to draw before action 19.3% and after the acthad increased by74.9%, 4)the ability toexplain the concepts before and after the 9.6% action action increased by 61.2%. Based on this study concluded that the implementation of contextual teaching and learning strategies to improve communication student learning in mathematics learning in class VIII BSMP Muhammadiyah 10 Surakarta.